STRATEGI PENUNJANG ADOPSI TEKNOLOGI M-COMMERCE B2C DI INDONESIA (LAZADA, ZALORA DAN BHINNEKA) - Tjahyana, Lady Joanne (Scriptura, 2015)
Indonesia is a country with significant amount of mobile commerce (m-commerce) users in Asia Pasific, supported by the growth of m-commerce providers especially in Business to Consumer (B2C) sector. The m-commerce services in Indonesia are availabe on mobile application and mobile friendly version of the e-commerce websites. This research was conducted to see the strategies being used by the m-commerce providers to support the factors of m-commerce adoption in Indonesia. The method used in this research was qualitative content analysis using m-commerce adoption factors, which are trust, cost, social influences, variety of services, perceived usefulness, perceived ease of use, and trialability. The objects of this research are the top 3 of the most popular B2C online shops in Indonesia with Alexa Rank below 100. Those online shops are Lazada, Zalora and Bhinneka. The conclusion of this research was that those B2C online shops have applied their strategies to support the m-commerce adoption factors on mobile applications as well as on mobile friendly version of their e-commerce websites.